MODEL OF FOREIGN LANGUAGE EXPLORATORY (FLEX) PROGRAM FOR ELEMENTARY LEVEL - Tintin Susilowati (Ibriez: Jurnal Kependidikan Dasar Islam Berbasis Sains)
Teaching English for elementary schools in Indonesia has been taught since 1994, however, the quality of the learning is still far from satisfactory results. Therefore, teaching English on this level should be developed meaningfully by promoting the learning contexts effectively because it directly influences the students’ competence and attitudes toward the target language on the next levels. This is a library research article with the aim to design a model of a language program conducted by analyzing 10 relevant articles through library research tools. The instruments of this research were observation sheets to organize the data from the articles and documentary analysis was applied to analyze the data. Foreign Language Exploratory Program (FLEX) is a form of alternative language program used to facilitate the students to have a better understanding of world languages on their ages. Therefore, the question to be addressed in this paper is “How is the appropriate model of a FLEX Program to boost motivation in learning English for elementary level?” The discussion of such a question is worthy to do to produce an interesting model that is relevant with the young foreign language learners since the young learners are parts of global citizen in the future life.